Self-Care Management Among Hypertensive Elderly: A Descriptive Study of Knowledge, Attitudes, and Practice - Deskrisman Stefan Mendrofa (Sean Institute, 2026)
Hypertension in the elderly is a serious health issue that can lead to fatal complications if not managed through proper self-care. This descriptive quantitative study aims to describe the knowledge, attitudes, and practices of elderly hypertensive patients at UPT Puskesmas Medan Johor. Data were collected using questionnaires from 64 respondents selected via accidental sampling. Inclusion criteria included elderly aged ≥ 60 years with blood pressure ≥140/90 mmHg. The majority of respondents were female (58%) and in the 60–74 age group (78%). The results showed that the respondents' knowledge level was in the good category (61%), attitudes in the good category (50%), and practices in the good category (70%). However, barriers were still identified in the male elderly group, who sought health check-ups less frequently than females. The high percentage of good behavior is influenced by the respondents' education level, which is mostly secondary (high school). Adequate knowledge forms positive perceptions (attitudes), which in turn triggers routine self-care practices. In conclusion, the elderly at UPT Puskesmas Medan Johor exhibit high self-awareness, but specific interventions are needed to increase male elderly participation in hypertension management.